Genetic Diversity of White-spotted Rabbitfish (Siganus canaliculatus) on Different Seagrass Habitats in Inner Ambon Bay, Indonesia Based on Mitochondrial CO1 Sequences - Husain Latuconsina,; Nurlisa A. Butet,; Ridwan Affandi,; M. Mukhlis Kamal,; Syamsul Bachry ,; Agus Alim Hakim , (Tropical Life Sciences Research, 2024)
This study aims to analyse the genetic diversity of Siganus canaliculatus in the Inner Ambon Bay (IAB) waters. DNA of S. canaliculatus specimens collected from IAB was extracted from tissues using a Tissue Genomic DNA Mini Kit, and partial CO1 genes were amplified using pair of universal primers. Genetic distances were determined by Kimura 2-parameter, and phylogenetic trees were constructed using the neighbour-joining method in MEGA 10.2.2 software. Arlequin software was used to analyse Fixation Index (Fst) and Analysis of Molecular Variance (AMOVA). There are three SNPs of S. canaliculatus from IAB that distinguish GenBank sequence data from S. canaliculatus. In Tanjung Tiram population group, contained three specific 677 (A), 679 (G), 703 (T) sites and two 693 (G), 714 (A) sites for the Nania population. Haplotype and nucleotide diversity of each population range from 0.000 to 1,000 and 0.000 to 0.004. Intra- and inter-population genetic differentiation were 21.19% dan 78.81%, respectively. Intra- and inter-population genetic distances were in range of 0.40–1.13 and 0.00–0.37, respectively. The pattern and direction of tidal currents as a link or barrier to spatial distribution and connectivity of S. canaliculatus larvae between seagrass habitats, as well as the presence of different anthropogenic pressures in each seagrass habitat, are thought to influence the genetic characteristics (genetic diversity, genetic variation, genetic differentiation and genetic distance) of S. canaliculatus populations in IAB waters. The results of this study provide information about the urgency of habitat-based fisheries management to support sustainable utilisation.